Notoginseng Triterpenes Inhibited Autophagy in Random Flaps via the Beclin-1/VPS34/LC3 Signaling Pathway to Improve Tissue Survival - Huang, Zhiyang; Luo, Xiaobin; Zhang, Yifan; Ying, Yibo; Cai, Xiong; Lu, Wenjie; Zhao, Juan; Wang, Yutian; Lin, Wenwei; Tu, Yurong; Xiang, Ziyue; Wu, Qiuji; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Random flaps are widely used in tissue reconstruction, attributed to the lack of vascular axial limitation. Nevertheless, the distal end of the flap is prone to necrosis due to the lack of blood supply. Notoginseng triterpenes (NTs) are the active components extracted from Panax notoginseng, reducing oxygen consumption and improving the body’s tolerance to hypoxia. However, their role in random flap survival has not been elucidated. In this study, we used a mouse random skin flap model to verify that NT can promote cell proliferation and migration and that increasing blood perfusion can effectively improve the survival area of a skin flap. Our study also showed that the autophagy of random flaps after NT treatment was activated through the Beclin-1/VPS34/LC3 signaling pathway, and the therapeutic effect of NT significantly decreased after VPS34 IN inhibited autophagy. In conclusion, we have demonstrated that NT can significantly improve the survival rate of random flaps through the Beclin-1/VPS34/LC3 signaling pathway, suggesting that it might be a promising clinical treatment option.